In situ spectroscopy of ligand exchange reactions at the surface of colloidal gold and silver nanoparticles. (15th February 2017) - Dinkel, Rebecca; Peukert, Wolfgang; Braunschweig, Björn
Abstract: Gold and silver nanoparticles with their tunable optical and electronic properties are of great interest for a wide range of applications. Often the ligands at the surface of the nanoparticles have to be exchanged in a second step after particle formation in order to obtain a desired surface functionalization. For many techniques, this process is not accessible in situ . In this review, we present second-harmonic scattering (SHS) as an inherently surface sensitive and label-free optical technique to probe the ligand exchange at the surface of colloidal gold and silver nanoparticles in situ and in real time. First, a brief introduction to SHS and basic features of the SHS of nanoparticles are given. After that, we demonstrate how the SHS intensity decrease can be correlated to the thiol coverage which allows for the determination of the Gibbs free energy of adsorption and the surface coverage.